Analisa Pengaruh Partial Media Sosialdanatribut Produk Terhadap Citra Merekserta Keputusan Pembelian â€œJamur Mantanâ€ - Apsari Murlinawati; Ahsin Daroini; Ratna Dewi Mulyaning Tiyas (Manajemen Agribisnis: Jurnal Agribisnis, 2023)
Social media marketing is an online activity and program designed to engage businessman, customers or prospects and directly raise awareness, improve product attributes, establish a brand image, or gain product sales.The objectives of the study were (1) to determine the partial effect of social media (X1) and product attributes (X2) on the brand image (Y) of the â€œjamur mantanâ€ snack and (2) to determine the partial of social media (X1), product attributes (X2) and brand image (Y) on purchasing decisions (Z) â€œjamur mantanâ€ snack. Type of research is descriptive research with a quantitative approach. Data collection was carried out by distributing closed questionnaires with 5 Likert scales. Data were analyzed using SPSS, the tests conducted were validity, reliability and t test. Based on the results of the study, it was found that the validity and reliability tests were obtained that the instruments used were valid (rcount â‰¥ 0,3) and reliable (Cronbach's Alpha value â‰¥ 0,6. The results of partial hypothesis testing are that brand image is significantly affected by product attributes, while social media has no significant effect. Purchase decisions are significantly influenced by social media. Brand image has an effect on purchasing decisions but is not significant, while product attributes have no effect.